Interventions for inclusive and efficient value chains: Insights from CGIAR research - de Brauw, Alan; Bulte, Erwin (International Food Policy Research Institute, 2021)
Efforts to promote the development of agricultural value chains are a common element of strategies to stimulate economic growth in low-income countries. Since the world food price crisis in 2007-2008, developing country governments, international donor agencies, and development practitioners have placed additional emphasis on making agricultural value chains work better for the poor. As value chains evolve to serve new markets, they tend to become less inclusive. For example, if a market for high quality rice arises within an economy, it is inherently easier for traders who sell rice to retailers to source that high quality rice from larger farms that are better able to control its quality than from dozens of smallholder farms. As a result, the normal path of value chain evolution can be biased against smallholders; hence, it is important to understand what types of interventions can make value chains more inclusive while also making them more efficient. In this brief, we summarize studies on five types of value chain interventions that were supported by the CGIAR’s Research Program on Policies, Institutions, and Markets (PIM) through its Flagship 3 on Inclusive and Effective Value Chains. Figure 1 illustrates a “typical” agricultural value chain, including the five intervention types (in orange). These include interventions that attempt to deal with multiple production constraints; certification; contract farming; public-private partnerships; and “other” services related to trading and marketing agricultural products. Apart from the last category, these interventions all involve production. This reflects the fact that smallholder producers can be considered, in some ways, the weakest link in evolving agricultural value chains (de Brauw and Bulte 2021). Hence, it is sensible to target interventions either at or close to smallholders. However, in some cases, the best way to overcome smallholder constraints may be to help actors at other points in the value chain overcome constraints. Many interventions share a focus on reducing transaction costs to promote smallholder market integration. Ideally, interventions increase both efficiency and inclusion, but we observe that such win-win outcomes are rare. Trade-offs appear to be more common than synergies, and some value chain interventions involve clear winners and losers.